A Common Operating Picture for Air Force Materiel Sustainment First Steps - Pyles, Raymond A. (RAND Corporation, 2008)
Describes a potential common operating system (COP) for the Air Force materiel sustainment system (MSS). The authors first develop a COP based on the principles of effects-based measures, schwerpunkt (organizational focus), decision rights, and a nonmarket economic framework, then they apply the COP to depot-level reparable component sustainment to illustrate how the COP would improve overall MSS efficiency and responsiveness.